1995
DOI: 10.1128/aac.39.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Roles of divalent cations and pH in mechanism of action of nitroxoline against Escherichia coli strains

Abstract: The antibacterial activity of nitroxoline (NIT), an antibiotic used in the treatment of acute or recurrent urinary tract infections caused by Escherichia coli, is decreased in the presence of Mg 2؉ and Mn 2؉ but not Ca 2؉ . In order to elucidate the interaction between this drug and the divalent cations, spectrophotometric studies based on the natural absorption of the nitroxoline moiety were conducted. In the presence of the divalent metal ions, a shift in the NIT A 448 suggested the formation of drug-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 36 publications
(46 reference statements)
2
53
0
Order By: Relevance
“…A higher AUBT 24 in acidic urine for NTX was demonstrated only for E. coli ATCC 25922. The finding of more-pronounced antibacterial activity in an acidic environment for NTX was also shown in other investigations (18). Therefore, there should be a call for pH measurement if NTX is to be employed, or an acidifying agent may be added to NTX treatment to improve antibacterial activity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A higher AUBT 24 in acidic urine for NTX was demonstrated only for E. coli ATCC 25922. The finding of more-pronounced antibacterial activity in an acidic environment for NTX was also shown in other investigations (18). Therefore, there should be a call for pH measurement if NTX is to be employed, or an acidifying agent may be added to NTX treatment to improve antibacterial activity.…”
Section: Discussionmentioning
confidence: 88%
“…Its antimicrobial efficacy is based on its ability to chelate divalent cations (18). Although it has been in clinical use for many years, no increase in resistance has been observed for Escherichia coli, the most frequent uropathogen (19).…”
mentioning
confidence: 99%
“…Currently, attempts are under way to identify therapeutically applicable compounds that would show strong chelating properties without concomitant immunogenicity or toxicity (1,18,19). The antimicrobial effects of the urinary antibiotic nitroxoline have long been known to depend on its ability to chelate bivalent and trivalent cations (9,20). We thus examined the influence of nitroxoline on biofilm formation by the well-established laboratory model strain PAO1 and by three clinical P. aeruginosa aeruginosa isolates from different sources (see Table 1 for a description of strains).…”
mentioning
confidence: 99%
“…Nitroxoline is known to form a chelate with Mn 2+ (21 μM 5 + 10 mM MnCl 2 was used in this study; bathochromic and hypsochromic shifts were seen, λ max = 448 nm shifted to 430 nm), 24 and we also observed a measurable shift even at 10 μM (both 5 and MnCl 2 ). However, under the same conditions CoCl 2 caused a huge hypochromicity coupled with a bathochromic shift (450 nm to 435 nm).…”
Section: Resultsmentioning
confidence: 53%
“…The metal chelation property is thought to be the underlying cause for the bioactivity of cloxyquin and clioquinol, and it has been shown that nitroxoline shares that feature to manifest its antibacterial activity. 24 Herein, we report the structure–activity relationship (SAR) studies of the two oxines we identified as hits in the HTS by obtaining and evaluating different analogs through either purchasing from commercial source or synthesizing in-house. We characterized each analog in HUVEC proliferation assay using [ 3 H]-thymidine incorporation, and enzymatic assays with MetAP1 and MetAP2.…”
Section: Introductionmentioning
confidence: 99%